2021
DOI: 10.30621/jbachs.863206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workload Caused by the Pandemic on Depression, Anxiety and Stress Levels in Surgical and Operating Room Nurses

Abstract: have been taken by central authorities and health units around the world. However, it has spread rapidly and caused more than 75 million diagnoses and 1.6 million deaths globally (2). It is known that healthcare professionals are at serious risk and are infected with Covid-19 14 times more than other segments of the ABSTRACT Purpose: To determine the effect of pandemic workload on depression, anxiety and stress levels in surgical and operating room nurses. Methods: study is planed a descriptive and cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
4
0
6
Order By: Relevance
“…Araştırmanın verileri, konu ile ilgili literatüre dayalı olarak hazırlanan sosyodemografik özelliklerini içeren "hemşire tanıtım formu" 3,5,[12][13][14]16,17 ve hemşirelerin deneyimlerini belirlemek amacıyla oluşturulan "yarı yapılandırılmış görüşme formu" 13,14,16…”
Section: Veri Toplama Araçlarıunclassified
See 2 more Smart Citations
“…Araştırmanın verileri, konu ile ilgili literatüre dayalı olarak hazırlanan sosyodemografik özelliklerini içeren "hemşire tanıtım formu" 3,5,[12][13][14]16,17 ve hemşirelerin deneyimlerini belirlemek amacıyla oluşturulan "yarı yapılandırılmış görüşme formu" 13,14,16…”
Section: Veri Toplama Araçlarıunclassified
“…3 Aksoy ve Koçak (2020) yaptığı çalışmada psikolojik destek sağlama ve sağlık çalışanları için sürekli bir zihinsel sağlık izleme programlarının oluşturulması önerilmektedir . 18 16 Pandemide aktif olarak görev almaya teşvik etme, mesleki kimliklerini ve mesleki uygulamalarda doyum almalarını sağladığı bildirilmektedir. 17,24 Doyum sağlamanın yanı sıra pandemi sürecinde hemşirelerin hasta bakımında daha fazla insiyatif aldıkları ifade edilmektedir.…”
Section: Ekip Içi Iletişimunclassified
See 1 more Smart Citation
“…In the studies conducted, it was determined that surgical nurses had problems such as psychological problems such as anxiety, depression, stress, communication difficulties within the team, workload, inadequacy of material and moral support systems, as well as physical and social problems during the pandemic. [ 4 , 6 , 8 , 9 ]. Fereidouni et al [ 7 ] reported a significant relation between job satisfaction and adherence to preventive guides during COVID-19 pandemic in operating room nurses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have not been any studies on factors affecting COVID-19-related fear and burnout in surgical nurses. It is stated in the literature that psychological status of surgical nurses during the pandemic can affect perioperative care [ 9 ]. Therefore, the present study focused on COVID-19-related fear and burnout levels and affecting factors in surgical nurses.…”
Section: Introductionmentioning
confidence: 99%